101 A Posture and Mobility Training Package for Care Home Staff: Results of A Cluster Randomised Controlled Feasibility Trial. (6th February 2020) - Graham, L; Cundill, B; Ellwood, A; Fisher, J; Goodwin, M; Hawkins, R; Holland, M; Hull, K; Hulme, C; Kelly, C; Williams, R; Farrin, A; et al.
Abstract: Introduction: Provision of care for care home residents with complex needs is challenging. Physiotherapy and activity interventions can improve physical well-being but are often time-limited and resource intensive. A sustainable approach is to enhance the confidence, skills and abilities of care home staff. This trial assessed the feasibility of undertaking a definitive evaluation of the Skilful Care Training Package (SCTP) - a posture and mobility training programme developed by physiotherapists for care home staff. Methods: A parallel-group, cluster randomised controlled feasibility trial was undertaken in ten care homes in Yorkshire. Five were randomised to receive SCTP, five to usual care. SCTP was delivered by specialist physiotherapists, with the intention of training all direct care staff. Following consent, data were collected from and about residents with restricted mobility (those fulfilling the eligibility criteria) at baseline, three and six months post-randomisation by blinded researchers. Outcome measurement included resident mobility, posture, pain and quality of life. The feasibility of recruitment, retention, data collection and intervention delivery was assessed. Results: All residents (348) at participating homes were screened for eligibility. 250 were eligible and 146 took part. Follow-up was balanced between arms, with an overall loss-to-follow-up rate of 28.8% at six months. Where residents were available for six-month follow-up, proxy data provision was excellent (97.1% - 100% of expected data). Difficulty collecting data directly from residents was experienced (43.3% of expected data) due to high levels of cognitive impairment. Staff attendance at training met or was close to pre-specified criteria for acceptability in three homes, with 63.0%, 63.6% and 65.8% direct care staff attending all sessions, and >85% attending at least one session across all three homes. However attendance fell short of acceptability in two homes, with only 21.4% and 12.5% staff attending all sessions. Conclusions: It is feasible to recruit and follow-up residents in a randomised trial comparing SCTP and usual care. Proxy data collection is a successful method, but collection of data from residents is difficult. Intervention delivery success was variable, illustrating heterogeneity between care homes. Future research will be informed by learning from those homes with greater intervention compliance. Work should be undertaken to investigate how best to collect meaningful data from residents.